Efficient light harvesting with double-sided anodic titania nanotube arrays in dye-sensitized solar cells - Sun, Lidong (2011)
In the past decade, anodic titania nanotube arrays have been vigorously investigated in dye-sensitized solar cells so as to reduce electron scattering and energy loss that present in conventional titania nanoparticle photoanodes. However, the photovoltaic efficiency of the cells based on the nanotubes is not as efficient as that on the nanoparticles. This is due to the low photocurrent induced by the low dye loading amount of the nanotube photoanodes. As such, in this project a novel parallel configuration of dye-sensitized solar cells is proposed on the basis of double-sided nanotubes. To achieve the parallel structure, anodic nanotube growth is studied first with reference to electric field which is believed to be an essential factor influencing the tube geometry, although the geometry has been reported to be affected by a number of factors (e.g., applied potential, working distance, water content, temperature, and so forth). Electric field originating from the potential drop over the oxide layer results in linear increase in pore diameter while exponential increment in growth rate. Electric field emanating from the potential drop in the organic electrolyte also contributes to the growth rate by promoting the ionic flux in the electrolyte. The effect of the field can be explained by an ion flux model. More detailed investigation on the role of electric field in the electrolyte is carried out by double-sided nanotube growth. Nanotube arrays are grown simultaneously on both sides of a titanium foil using a typical two-electrode method. Tube length at the frontside is longer than that at the backside, as a consequence of higher ionic flux induced by the electric field at the frontside. The tube length is thus tailored to be comparable at both sides through adjusting the field. Transition from nanotubes to nanowires is investigated subsequently in order to obtain clear tube surface suitable for application in dye-sensitized solar cells. The results demonstrate that the transition requires a large number of hydrogen ions to reduce the passivated area of tube walls, therefore can be observed only under an intermediate chemical dissolution environment. Ultrasonic cleaning is found effective in clearing away the nanowires on top of the nanotubes due to formation of quasi-nanosprings. The parallel configuration of dye-sensitized solar cells is achieved using the double-sided nanotubes as the photoanodes. The photovoltaic performance of the cells exhibits an average 70% increment in photocurrent and 30% enhancement in conversion efficiency, as a consequence of highly increased surface area and considerably reduced series resistance. A theoretical calculation and relevant fitting results indicate that a tube length of ~30 microns is optimal for the nanotubes used in the current work. This parallel structure is effective in promoting the light harvesting of dye-sensitized solar cells based on anodic nanotube arrays.